Physicochemical and biological characterization of leachate from the uncontrolled final disposal site in Tlapacoyan, Veracruz, Mexico - López Ramírez, Miguel Angel; Aburto Gutiérrez, Yasser Armando; Ocaña Drouaillet, Keila Elena; Olaya Pirene, Castellanos Onorio; Reynoso, Fabiola Lango; Ramírez, Maribel López (Enfoque UTE, 2022)
One of the main problems in Mexico is contamination by leachates that are produced in final waste disposal sites, since they are highly toxic and damage the biota. This research focuses on determining the characteristics of the leachate produced in the uncontrolled final disposal site in the municipality of Tlapacoyan, Veracruz (Mexico). As a result, it was determined that the parameters that cause damage to the biota are total nitrogen (152.759 mg L-1), mercury (0.006 mg L-1), cadmium (0.003 mg L-1), copper (0.052 mg L-1), chromium (0.0731 mg L-1), nickel (0.0524 mg L-1), lead (0.005 mg L-1) and total coliforms (> 2 400 MPN), as they do not meet at least one of the national and international standards of maximum permissible limits. Likewise, it was determined that the leachate produced at this site is of the mature and poorly biodegradable type (BOD/COD=0.018), so that the typical or bioremediation methods are not recommended for its treatment.